A Critique of the Tradition of Qurbani Meat Distribution in Temanggung from the Perspective of Shāfiʿī Fiqh - Muh. Syakur; Marsudin; Muhammed Zaki Tamami; Sumarjoko (Jurnal Syariah, Hukum, dan Ekonomi Islam, 2024)
The tradition of distributing sacrificial meat in Sidoharjo Village, Candiroto District, Temanggung Regency, begins with the sacrificial shohibul coming to the slaughterer to slaughter the sacrificial animal on Eid al-Adha. The head of the sacrificial animal must be given to the slaughterer as wages (ujrah) for his slaughtering services. This tradition has been carried out since ancient times, under the pretext of not burdening the sacrificial shohibul in paying wages to the slaughterer. This study aims to find out more about the implementation of the tradition of distributing sacrificial animal meat in Sidoharjo Village, Candiroto District, Temanggung Regency. And to find out the review of Syafi'i jurisprudence on this matter. This research is field research, using descriptive qualitative methods, by collecting, analyzing and interpreting data. Data collection techniques were carried out using primary data obtained from interviews with research subjects. Secondary data sources were obtained from books, journals, theses and articles. Data collection and analysis is carried out to obtain the existing reality. The results of the research found that the Syafi'i School of Islamic Scholars agree that it is haram to give wages to the slaughterer from the body parts of the sacrificial animal. Such as meat, skin, head or something else. The sacrificial service basically aims to offer devotion to Allah SWT, so the sacrificial meat should be given in charity to those who are entitled to it and to obtain blessings, it is sunnah for the sacrificial shohibul to eat the sacrificial meat in moderation.